A study of the optimum level of fertilizer and spacing required to good quality babchi (Psoralea corylifolia L.) - Ravi, Virat K.; Kohli, Subhas; Khan, Aamir Mirza (Global Journal of Food and Agribusiness Management, 2017)
Nutrient management and maintenance of optimum number of plants per unit area are considered as important management tool for enhancing the productivity of crop plants. Therefore this experiment was conducted to identify the optimum level of NPK fertilizer and spacing required for obtaining higher seed yield with quality in underutilized medicinal plant babchi (Psoralea corylifolia L.). The evaluation was conducted with three different NPK fertilizers levels (80:40:30, 100:60:50 and 120:80:70 kgha-1 ) and four different spacings (45×30, 45×45, 60×30 and 60×45 cm) in two seasons viz., kharif and rabi. Significant variations were observed in most of the observed parameters, it expressed that the fertilizer recommendation of NPK at 100:60:50 kgha-1 , adopting the spacing of 60×30 cm maximized the seed yield upto 2404 kg ha-1 with the resultant seed germination of 43%. It was 27.6% higher than 80:40:30 kg ha-1 NPK. The protein (18.69%) content of the seeds was also higher with these management techniques in both the seasons. Therefore the optimum fertilizer recommendation of 100:60:50 kgha-1 NPK and spacing of 60×30 cm could be recommended for babchi seed production.